PEMETAAN FAKTOR RESIKO STUNTING PADA IBU HAMIL DI UPT PUSKESMAS PAL LIMA - Selviana; Yoga Prakasa Putra; Linda Suwarni (Public Health Department, Faculty of Health Science University Muhammadiyah Bengkulu, 2023)
Backgorund: Stunting incidence in Indonesia is 21.6% which is still quite high compared to the target in 2024 of 14%. Primary prevention efforts are essential in reducing the number of stunts through mapping stunting risk factors in pregnant women so that intervention programs can be carried out as a stunting prevention effort. Objective: This study aims to map the risk factors of stunting in pregnant women in the UPT Puskesmas Pal V Town of Pontianak. Method: This research includes observational research with a descriptive approach. The popilation of this study is the entire pregnant women by 2023 in the UPT Puskesmas Pal V city of Pontianak, which is a total of 22 people. The sample used total sampling. Cata analysis uses univariates by describing risk factors in percentage and in mapping from. Result: The study obtained 20.9% had anemia in mothers, 13.6% had Chronic Energy Deficiency (CED), and the age at risk was less than 20 years old (22.7%). Conclusion: Support is needed in pregnant women who are at risk of having a stunting child by local health woorkers so that they can prevent a child born from having stunting at age 2 years old.eywords : Prevention Model, Local Wisdom, Stunting, Mapping Stunting Risk Factor